Effect of the botulinum toxin injections and endoscopic pneumocardiodilation on symptoms severity and treatment outcomes among patients with primary esophageal sphincter achalasia - Kiosov, A. (Journal of Education, Health and Sport, 2021)
Achalasia is a disorder of esophageal motility, which is manifested by symptoms of dysphagia, belching undigested food, respiratory symptoms (night cough, recurrent aspiration and pneumonia), chest pain and weight loss. Aim of the study. To determine the possibilities and clinical effectiveness of combined approaches in the treatment of cardiac achalasia using endoscopic pneumocardiodilation and injections of botulinum toxin type A "Dysport" at various stages of the disease. Materials and methods. Injections of the drug botulinum toxin type A "Dysport" and balloon endoscopic pneumocardiodilation (EPCD) were used. The contents of the vial with botulinum toxin were diluted in 0.9% sodium chloride solution to obtain a solution containing 60 UA in 1 ml. In each of the four quadrants of the LES, 2 injections of 0.5 ml of the drug "Dysport" were made with a concentration of a solution of 30 UA in 0.5 ml at a distance of 1 cm from one another. The total dose was 250 units. The technique of isolated EPCD, was carried out with a Witzel balloon dilator, 40 mm in diameter, it required a thorough preoperative examination of the patient, including an assessment of the general condition, the presence and severity of body weight deficiency, water-electrolyte, protein, achlorhydric manifestations of the disease, as well as the propulsive ability of the esophagus through X-ray examination. Results. The combined endoscopic method significantly improves the results of treatment of esophageal cardiac achalasia, having a direct impact on the pathogenetic mechanisms of its development. Given the effectiveness of treatment of esophageal cardiac achalasia by botulinum toxin injection and pneumocardiodilation, this method can be used in patients with comorbid pathology and high surgical risk as an alternative to laparoscopic Heller procedure (cardiomyotomy), especially in older patients. Unsatisfactory results of the combined endoscopic method of treatment of stage III-IV cardiac achalasia for up to 2 months are an indication for surgical treatment of this pathology. Conclusions. Given the significant increase in knowledge about this nosology in recent years, there is a need for a comprehensive, evidence-based study of new promising treatments for patients, covering all aspects of the disease.